The Rhetoric of The Instagram Account @Gusmiftah's Dakwah in Broadcasting Religious Moderation - Indah Ardianti; Azhar (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2025)
This study aims to analyze the preaching rhetoric used by the Instagram account @gusmiftah in spreading the values ​​of religious moderation. Using a descriptive qualitative approach and content analysis, this study examines three video uploads of Gus Miftah's preaching and audience responses. The results show that Gus Miftah effectively applies three elements of Aristotle's rhetoric: ethos (credibility as a cleric), pathos (emotional power through persuasive language), and logos (logical argumentation supported by Quranic verses) to convey messages of religious moderation such as tolerance, unity, and anti-extremism. Despite some criticism, the majority of audience responses are positive, demonstrating the effectiveness of his digital preaching strategy. This study concludes that Aristotle's rhetoric is still relevant in the context of digital preaching and can serve as a model for preachers in spreading moderate Islam on social media.